2000
DOI: 10.1590/s0100-204x2000000100019
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização química da carne de cabrito da raça Moxotó e de cruzas Pardo Alpina x Moxotó

Abstract: O objetivo da pesquisa foi avaliar a composição química da carne de cabrito-mamão (idade média de 72 dias), da raça Moxotó (MOX), grupos genéticos ¾ Pardo Alpina x ¼ Moxotó (3/4 PAMOX) e ½ Pardo Alpina x ½ Moxotó (1/2 PAMOX). A análise apresentou valores médios entre 77,80% a 80,25% de umidade; 15,90% a 19,08% de proteína; 1,12% a 1,21% de gordura, e 1,29% a 2,03% de cinzas. Quanto à composição mineral, os valores médios variaram de 5,62 mg/100 g a 8,21 mg/100 g de cálcio; 156,97 mg/100 g a 196,25 mg/100 g de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
2
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
(11 reference statements)
5
3
2
6
Order By: Relevance
“…Ash, moisture and protein values were close to those presented in literature (Dhanda et al, 1999(Dhanda et al, , 2003Madruga et al, 1999bMadruga et al, , 2001Beserra et al, 2000Beserra et al, , 2004Silva, 2005) and vary from 0.79 to 1.68%, from 70.80 to 80.25% and from 18.50 to 23.39%, respectively. Hashimoto et al (2007) found that the centesimal composition of the longissimus dorsi muscle of sheep was not affected by the substitution of corn by soybean hulls, which was not observed in this study.…”
Section: Resultssupporting
confidence: 88%
“…Ash, moisture and protein values were close to those presented in literature (Dhanda et al, 1999(Dhanda et al, , 2003Madruga et al, 1999bMadruga et al, , 2001Beserra et al, 2000Beserra et al, , 2004Silva, 2005) and vary from 0.79 to 1.68%, from 70.80 to 80.25% and from 18.50 to 23.39%, respectively. Hashimoto et al (2007) found that the centesimal composition of the longissimus dorsi muscle of sheep was not affected by the substitution of corn by soybean hulls, which was not observed in this study.…”
Section: Resultssupporting
confidence: 88%
“…The other components of the proximate analysis performed in this study did not differ between diets. Moisture, protein and ash values were close to those found in the literature for this species (DHANDA; TAYLOR; MURRAY, 1999, DHANDA;et al, 2003;ARRUDA;NASCIMENTO, 1999, MADRUGA et al, 2001BESERRA et al, 2000BESERRA et al, , 2004, ranging from 70.80 to 80.25 %, 18.50 to 23.39 % and 0.79 to 1.68 %, respectively. The fatty acid profile of meat is important to human health because people can reduce their risks of obesity, cancer and heart diseases by reducing lipid intake, especially cholesterol and saturated fatty acids, and increasing the consumption of monounsaturated and polyunsaturated fatty acids (JAKOBSEN, 1999;RHEE et al, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…Ao fazer-se uma comparação dos valores em magnésio na carne caprina reportados na literatura por BESERRA et al (2000); BESERRA et al (2001);TIMBÓ, (1996); PARK (1990);CASEY (1992), observa-se uma baixa concentração deste mineral na carne. Este fato poderá ser explicado pela eimeriose que acometeu os animais durante a fase experimental.…”
Section: Resultsunclassified
“…O baixo conteúdo de Ferro aqui obtidos (1,29 a 2,17mg/100g), que é inferior aos reportados para caprinos do Nordeste Brasileiro por MADRUGA, (1999( ) e BESERRA et al(2001, coincide com teores citados por BESERRA et al (2000) e ZAPATA et al (1995. Este fato era esperado ao considerar-se o plano nutricional pobre em ferro a que foram submetidos.…”
Section: Resultsunclassified
See 1 more Smart Citation